Influence factors studies on the Rh-Catalyzed asymmetric transfer hydrogenation of ketones with surfactant-type ligand in water. Issue 3 (18th January 2019) - Li, Jiahong; Han, Jie; Lin, Zechao; Tang, Lei; Huang, Qingfei; Wang, Qiwei; Zhu, Jin; Deng, Jingen
Abstract: The influence factors of surfactant-type catalysts system on the asymmetric transfer hydrogenation (ATH) of ketones in water, including the length of aliphatic tail, the concentration of catalysts and the solvent, have been investigated. These factors played significant roles on reaction activity and stereo control. With single-chain surfactant-type catalyst Rh-L4, α, β -unsaturated ketones especially the aliphatic derivatives affords excellent regioselectivities and enantioselectivities. Graphical abstract: